2017
DOI: 10.1111/jpc.13511
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between concern about autism spectrum disorder at the time of referral and diagnosis, and factors associated with agreement

Abstract: Referral for ASD diagnostic assessments in the cases where ASD is not the primary cause for a child's difficulties increases pressure on assessment services, can delay access to ASD-specific intervention services for children who do have ASD, and can contribute to parent anxiety unnecessarily. The current evidence that a substantial minority of children were referred for ASD diagnostic assessments when ASD was not the primary cause for the difficulties emphasises the value of adopting a developmental differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The remaining 20 children all met our inclusion criterion of either a formal diagnosis of autism ( n 14) or an ongoing formal diagnostic assessment ( n 6), which has an average duration for this age range of 3.5 years (Crane, Chester, Goddard, Henry, & Hill, ). In one large‐scale study, 70% of children referred for an autism diagnosis went on to receive a diagnosis, and for children without any co‐occurring conditions (as was the case for the present sample) this figure rose to 89% (Lo, Klopper, Barnes, & Williams, ). Importantly, all parents completed the Gilliam Autism Rating Scale (GARS) with all 20 children in the ASD group receiving GARS‐AI scores ≥71 (i.e., severity level 2 or 3).…”
Section: Methodsmentioning
confidence: 48%
“…The remaining 20 children all met our inclusion criterion of either a formal diagnosis of autism ( n 14) or an ongoing formal diagnostic assessment ( n 6), which has an average duration for this age range of 3.5 years (Crane, Chester, Goddard, Henry, & Hill, ). In one large‐scale study, 70% of children referred for an autism diagnosis went on to receive a diagnosis, and for children without any co‐occurring conditions (as was the case for the present sample) this figure rose to 89% (Lo, Klopper, Barnes, & Williams, ). Importantly, all parents completed the Gilliam Autism Rating Scale (GARS) with all 20 children in the ASD group receiving GARS‐AI scores ≥71 (i.e., severity level 2 or 3).…”
Section: Methodsmentioning
confidence: 48%
“…We included 56 studies that reported the mean and/or median age at ASD diagnosis, of which 46 reported an overall ASD mean age at diagnosis between 30.9 and 574.4 months (Becerra-Culqui et al, 2018; Begeer et al, 2013; Bello-Mojeed et al, 2017; Bent et al, 2015; Berg et al, 2018; Bravo Oro et al, 2012; Brett et al, 2016; Carias & Wevrick, 2019; Cawthorpe, 2018; Crane et al, 2016; Daniels et al, 2017; Darcy-Mahoney et al, 2016; Emerson et al, 2016; Garrido et al, 2018; Goodwin et al, 2017; Hagberg & Jick, 2017; Hall-Lande et al, 2018; Hausman-Kedem et al, 2018; Höfer et al, 2019; Hrdlicka et al, 2016; Jo et al, 2015; Kentrou et al, 2019; Kurasawa et al, 2018; Lagunju et al, 2014; Larsen, 2015; Lo et al, 2017; Magaña et al, 2013; Manohar et al, 2019; Martinez et al, 2018; Masri et al, 2013; May et al, 2017; Mazurek et al, 2014; Miodovnik et al, 2015; Mishaal et al, 2014; Mpaka et al, 2016; Ribeiro et al, 2017; Rutherford et al, 2016; Salomone et al, 2016; Sheldrick et al, 2017; Shrestha et al, 2019; Sicherman et al, 2017; Talero-Gutiérrez et al, 2012; Ververi et al, 2012; Wei et al, 2018; Zablotsky et al, 2018). Of the 56 studies, 24 reported an overall ASD median age at diagnosis (only or combined with mean age at diagnosis score) between 28 and 96 months (Baio et al, 2018; Becerra-Culqui et al, 2018; Bent et al, 2015;…”
Section: Resultsmentioning
confidence: 99%
“…Factors associated with age at ASD diagnosis. Of the 56 studies, 10 did not report any influencing factors on age at diagnosis (Cawthorpe, 2018;Garrido et al, 2018;Hausman-Kedem et al, 2018;Lo et al, 2017;Martinez et al, 2018;Masri et al, 2013;May et al, 2017;Mpaka et al, 2016;Nadeem et al, 2019;Ribeiro et al, 2017). However, 46 studies reported many possible influencing factors on age at ASD diagnosis, including type of ASD diagnosis, additional diagnoses and gender among the most frequently reported (Supplemental Material 2).…”
Section: Additional Analysesmentioning
confidence: 99%
“…The dissociation between parental opinion about child’s problems and objective status is common in ASD [ 33 ]. Parental collaboration in the diagnostic evaluation is rated by Bulgarian physicians as moderate—3, 2–3, 4 in a 1 to 5 scale [ 16 ].…”
Section: Discussionmentioning
confidence: 99%